PERANCANGAN RE-BRANDING UMKM BAKEDAY.CO DENGAN METODE MOSER UNTUK MENINGKATKAN BRAND AWARENESS - Sulianto, Katherin Agatina; Pratama, Bintang Pramudya Putra; Rahmadyanto, Sultan Arief (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2024)
Micro, Small, and Medium Enterprises (MSME) significantly boost the ecoomy in Indonesia. One of the sectors within MSME that is highly favored is the culinary industry. Particulary, the food industry operates indifinitely and remains ever present. Recently, culinary delights such as cakes and desserts have become a trend, presenting lucrative opportunities for sales. Bakeday.co in Malang Cilty is one such example. In any business endeavor, competition with peers is inventable, which Bakeday.co experiences, especially in building brand awareness. Therefore, establishing a strong brand identity through precise planning becomes crucial. For the brand identity design of Bakeday.co, the Moser method is employed, focusing on core brand values, core brand messages, and brand personality.